KOMPATIBILITAS PERBANYAKAN SECARA OKULASI BIBIT DURIAN (Durio zibethinus Murr) YANG DIBERI AIR KELAPA SEBAGAI ZAT PENGATUR TUMBUH ALAMI - Kirnadi, Ari Jumadi; Zuraida, Ana; Ilhamiyah, Ilhamiyah (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2025)
This research was aimed at finding out the effect of soaking time for natural growth regulators in coconut water on the success of grafting (compatibility) in durian grafting techniques and how long the soaking time for buds is best for successful durian grafting. This research used an experimental method: a single factor Completely Randomized Design (CRD). The treatment tried was soaking time in coconut water with a concentration of 100%, for 0 minutes, 15 minutes, 30 minutes, 45 minutes, and 60 minutes. The research results showed that the length of soaking of durian shoots in coconut water as a naturally growing substance had no significant effect on both the success of grafting and the rupture of shoots in Durian plant grafting. The percentage of grafting success for each treatment ranged from 20% - 40%.  Long ago the buds broke.  The average length (days) of bud break between treatments ranged from 35 days to 48.5 days after attachment of the bud.